2010
DOI: 10.1590/s0037-86822010000300018
|View full text |Cite
|
Sign up to set email alerts
|

Malária em mulheres de idade de 10 a 49 anos, segundo o SIVEP- Malária, Manaus, Amazonas, 2003-2006

Abstract: RESUMO. Results: Over this period, 13,308 malaria cases were notified, of which 815 (6.1%) were among pregnant women. There was a gradual decrease in the absolute numbers of cases among pregnant and non-pregnant women. Regarding species, 14.3% of the notified cases were caused by Plasmodium falciparum; 85% by Plasmodium vivax and 0.6 % by both of them. The frequency of Plasmodium falciparum infection was greater among pregnant women than among non-pregnant women (p > 0.05). Although most of the cases lived in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 7 publications
0
7
0
4
Order By: Relevance
“…As principais complicações da malária na gravidez estão relacionadas à integridade do binômio mãe-feto. As alterações que decorrem da gravidez (principalmente as de cunho imunológico) fragilizam o organismo materno, tornando-o suscetível às formas mais graves da doença, sendo as mais frequentes o aborto e parto prematuro -principalmente em áreas de baixa a moderada transmissão 18 . Outras complicações como a malária cerebral, edema pulmonar, anemia grave, hipoglicemia, morte neonatal representam uma ameaça constante ao organismo materno 19 .…”
Section: Discussionunclassified
“…As principais complicações da malária na gravidez estão relacionadas à integridade do binômio mãe-feto. As alterações que decorrem da gravidez (principalmente as de cunho imunológico) fragilizam o organismo materno, tornando-o suscetível às formas mais graves da doença, sendo as mais frequentes o aborto e parto prematuro -principalmente em áreas de baixa a moderada transmissão 18 . Outras complicações como a malária cerebral, edema pulmonar, anemia grave, hipoglicemia, morte neonatal representam uma ameaça constante ao organismo materno 19 .…”
Section: Discussionunclassified
“…Out of the 13,308 malaria cases reported in Manaus from 2003 to 2006 among women aged 10–49 years, 6.1% were in pregnant women and 80% of these were due to P. vivax [86]. In 2007–2008, malaria cases diagnosed in pregnant women comprised 6.7% of fertile-age women in three municipalities located in the Amazon Region, 80% of which were due to P. vivax infection [87].…”
Section: Challenges For Malaria Elimination In the Regionmentioning
confidence: 99%
“…A study analyzed 13,308 cases of malaria notified to the Sistema de Informação de Vigilância Epidemiológica (SIVEP-Malária -Epidemiological Surveillance Information System) among women aged 10 to 49 years between 2003 and 2006. Among the registered cases, 6.1% occurred in pregnant women, and it was observed that 85% of the notifications were caused by P. vivax, 14.3% by P. falciparum and 0.6% were cases of mixed malaria infection 4 .…”
Section: Introductionmentioning
confidence: 99%